2023
DOI: 10.1177/13591045231155990
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Comorbidity and Perceived Complexity on Outcomes of Referrals to Children and Young Person Mental Health Services (UK): A Mixed Methods Vignette Study

Abstract: Children and young people (CYP) with long-term physical conditions (LTCs) are four times more likely to develop mental health disorders yet many cannot access Children and Young People’s Mental Health Services (CYPMHS) or evidence-based interventions. This study aimed to understand the reasons for this; presence of an LTC neurodevelopmental disorder, or service requirements. 79 CYP mental health practitioners were randomly assigned to read vignettes depicting a hypothetical referral letter for a child with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Previous research in other clinical populations has found that treatments labelled as CBT often lack the fundamental components required by the evidence base (Cowdrey & Waller, 2015 ; Stobie et al, 2007 ; Waller et al, 2012 ). Also of note was that those CYP with a physical health condition were less likely to be given CBT than those without, which is consistent with previous research and may reflect clinicians’ lack of confidence in using CBT with this group ( Byrne et al, 2023 ; Carroll et al, 2021 ). Behavioural parenting interventions are the NICE recommended treatment for disruptive behaviour disorders ( NICE, 2013b ) and these are frequently seen in CYP with neurological disorders ( Davies et al, 2003 ).…”
Section: Discussionsupporting
confidence: 85%
“…Previous research in other clinical populations has found that treatments labelled as CBT often lack the fundamental components required by the evidence base (Cowdrey & Waller, 2015 ; Stobie et al, 2007 ; Waller et al, 2012 ). Also of note was that those CYP with a physical health condition were less likely to be given CBT than those without, which is consistent with previous research and may reflect clinicians’ lack of confidence in using CBT with this group ( Byrne et al, 2023 ; Carroll et al, 2021 ). Behavioural parenting interventions are the NICE recommended treatment for disruptive behaviour disorders ( NICE, 2013b ) and these are frequently seen in CYP with neurological disorders ( Davies et al, 2003 ).…”
Section: Discussionsupporting
confidence: 85%
“…That said, there are several barriers that limit access to evidence-based mental health care for CYP with LTCs. These include a lack of trained therapists, work demands, time, transport and costs alongside a lack of understanding that CYP with LTCs respond to existing evidence-based treatments [ 16 18 ]. There are also structural barriers in terms of service support for example, who is permitted as a referrer, and increasingly stringent referral criteria for services with referral outcomes for CYP with LTCs often unknown [ 19 ].…”
Section: Background and Rationale (6a)mentioning
confidence: 99%